Efeitos da suplementação de diferentes doses de whey proteins sobre o dano hepático de ratos wistar sedentários - BARBOSA, Anne Karynne da Silva (2019)
Introduction: Whey proteins is extracted from the aqueous portion of milk during the cheese making process, totaling about 20% of the protein content, has high biological value and nutritional attributes widely studied over the years. Objective: To investigate at the final moment after 12 weeks of supplementation of whey proteins at doses of 2, 4 and 6g/kg/day if alterations in liver function biomarkers occurred in male adult sedentary Wistar rats. Materials and Methods: the animal research ethics committee (CEUA) of the Federal University of Maranhão (UFMA) approved the study as number 23115.001161 / 2017-85, the sample consisted of 42 wistar rats with body weight of 200-250g and age of 60 days, divided in four groups: control group n=10 (C), supplemented group 2g/kg/day n=10 (W2), supplemented group 4g/kg/day n=7 (W4), and supplemented group 6g/kg/day n=5 (W6), supplemented through gavage with Whey Proteins was done daily, in divided doses in three sessions, with an interval of one hour (mean time of gastric emptying), during 12 weeks. Results and discussion: As for biomarker analysis values, Alanine aminotransferase, Aspartate Aminotransferase, Alkaline Phosphatase, Gamma Glutamyltransferase, Albumin, Total Protein, Bilirubin, although some groups showed differences among themselves, the overall result was not statistically significant, as was the histological analysis, which also did not show statistical significance. Conclusion: The findings of this study partially support the affirmative hypothesis (H0), which doses of 2, 4 and 6g/kg/day of whey proteins do not influence the loss of hepatic function, also responding to the objectives proposed in the present study.